Justifying power: when autocracies talk about themselves and their opponents. Issue 4 (8th August 2019) - Dukalskis, Alexander; Patane, Christopher
ABSTRACT: It is commonly understood that authoritarian regimes attempt to legitimize their rule and de-legitimize opponents. What is less clear is the intensity with which they do so, whether (de-)legitimation varies by institutional structure, and whether and how this intensity varies in times of crisis. To address these questions, this article focuses on the types of messages that autocracies disseminate, how they vary across autocratic regime types, and how they change when confronted with system-challenging movements. The article tests expectations using quantitative events data on government statements, movements and state repression. It also examines a case of a single-party regime faced with a widespread protest movement, namely China in 1989, to investigate whether the quantitative findings manifest themselves in the dynamics of a particular episode. The article finds evidence that autocratic regimes regularly disseminate messages to legitimize their rule and de-legitimize opponents and that single-party regimes generally engage in more (de-)legitimizing rhetoric than other autocratic regime types both during ordinary times and times of regime crisis. In general, regimes scale up their (de-)legitimation efforts when they face a major system-challenging movement as well as when they choose to repress such movements.